Kenaf Powder Filled Recycled High Density Polyethylene/Natural Rubber Biocomposites: The Effect of Filler Content - Cao, Xuan Viet; Ismail, Hanafi; A. Rashid, Azura; Takeichi, Tsutomu (International Journal of Integrated Engineering, 2012)
The performance of kenaf powder (KP) as filler for recycled high density polyethylene (rHDPE)/natural rubber (NR) thermoplastic elastomer (TPE) composites was investigated. The composites with different filler loading were prepared in a Haake internal mixer. Increasing KP loading in rHDPE/NR/KP biocomposites reduced the tensile strength, elongation at break but increased the stabilization torque and the tensile modulus. SEM study of fracture surface indicated that fibrillation of rHDPE was reduced and detachment of kenaf powder from polymer matrix was present particularly at high filler loading. These observations were responsible for the deterioration of tensile strength and elongation at break of rHDPE/NR/KP biocomposites. Water absorption study also showed that the water absorption of these biocomposites increased with increasing KP content.